Afterglow Nanoparticles: Coloring Afterglow Nanoparticles for High‐Contrast Time‐Gating‐Free Multiplex Luminescence Imaging (Adv. Mater. 49/2020). Issue 49 (8th December 2020) - Li, Zhanjun; Yu, Nuo; Zhou, Juanjuan; Li, Yang; Zhang, Yuanwei; Huang, Ling; Huang, Kai; Zhao, Yang; Kelmar, Sharon; Yang, Jinyi; Han, Gang
Abstract : Akin to "luminous pearls" in ancient Chinese tales of legend, afterglow nanoparticles display unusual extremely long‐life‐time luminescence properties after the cessation of excitation. In article number 2003881, Zhanjun Li, Gang Han, and co‐workers report multicolor afterglow "luminous pearls" with tailorable emission colors and uniform size. High‐contrast multichannel afterglow imaging can be readily accomplished without the current need of a time‐gating system.